PENGARUH DANA PERIMBANGAN DAN INVESTASI SERTA TENAGA KERJA TERHADAP PERTUMBUHAN EKONOMI WILAYAH KOTA DI PROVINSI KALIMANTAN TIMUR PADA ERA DESENTRALISASI FISKAL - Sunarto Mirman (LPPM University 17 Agustus 1945 Samarinda, 2017)
This study aims to analyze the effect of balanced funds, investment, and labor force to economic growth in urban areas of East Kalimantan Province during the period 2004 to 2008 and to identify the variable fund balance, investments, and the labor force, which variables are the dominant influence on economic growth in urban areas of East Kalimantan Province during the period 2004 to 2008 on Fiscal Decentralization Era. The results of data processing using SPSS for Windows find value of Coefficient of Determination (R Square) in the above calculation is for 0.654 or equal to 65.4%. While Adjusted R square (which is adjusted KD) of 0.589 means that 58.9 percent of the variance of economic growth in urban areas of East Kalimantan Province can be explained by the variance of the three independent variables in the model. Results of regression coefficients values for each independent variable on the entire observation area (urban area Samarinda, Balikpapan, Bontang and Tarakan) obtained is Y = 0.072 to 0.022 X1 + 0.002 X2 + 0.055 X3. It is estimated that the economic growth of urban areas in the province of East Kalimantan will decreased by 0.022 percent, if the fund balance has increased one unit (in billions). Also estimated that economic growth in the urban area of East Kalimantan province will experience an increase of 0.002 percent, if investment increases one unit (in billions).